Improved gut microbiome recovery following drug therapy is linked to abundance and replication of probiotic strains. (31st December 2022) - FitzGerald, Jamie; Patel, Shriram; Eckenberger, Julia; Guillemard, Eric; Veiga, Patrick; Schäfer, Florent; Walter, Jens; Claesson, Marcus J; Derrien, Muriel
ABSTRACT: Probiotics have been used for decades to alleviate the negative side-effects of oral antibiotics, but our mechanistic understanding on how they work is so far incomplete. Here, we performed a metagenomic analysis of the fecal microbiota in participants who underwent a 14-d Helicobacter pylori eradication therapy with or without consumption of a multi-strain probiotic intervention ( L. paracasei CNCM I-1518, L. paracasei CNCM I-3689, L. rhamnosus CNCM I-3690, and four yogurt strains) in a randomized, double-blinded, controlled clinical trial. Using a strain-level analysis for detection and metagenomic determination of replication rate, ingested strains were detected and replicated transiently in fecal samples and in the gut during and following antibiotic administration. Consumption of the fermented milk product led to a significant, although modest, improvement in the recovery of microbiota composition. Stratification of participants into two groups based on the degree to which their microbiome recovered showed i) a higher fecal abundance of the probiotic L. paracasei and L. rhamnosus strains and ii) an elevated replication rate of one strain ( L. paracasei CNCMI-1518) in the recovery group. Collectively, our findings show a small but measurable benefit of a fermented milk product on microbiome recovery after antibiotics, which was linked to the detection and replication of specific probiotic strains. Such functional insight can form the basis for the development of probiotic-based intervention aimed to protect gut microbiome from drug treatments.